EFIKASI TIGA JENIS RODENTISIDA ANTIKOAGULAN TERHADAP HAMA TIKUS PADA PERKEBUNAN KELAPA SAWIT - Samsuri Tarmadja; Servasius Adryan Ngidha (AGROISTA : Jurnal Agroteknologi, 2018)
The oil palm plantation may be suitable habitat for some wild small herbivore or omnivore species such as the rat. Rats are invasive pests in oil palm plantations, causing significant damages on fresh bunches fruit. Field efficacy studies using three anticoagulant rodenticides were conducted on rat pest of oil palms, at Jakluay Estate (JLYE) PT. Tapian Nadenggan (Sinarmas) Muara Wahau County, Kutai Timur District, Kalimantan Timur Province. Randomized Complete Block Design (RCBD) with two factor was applicated on the trial, that is three anticoagulant rodenticides and bait place position. Baiting manner with campaign method, one bait per palm, check and replenish bait points at every 4 days interval until 20 % replacement. Relative efficacies of various rodenticides and their bait place position were determined by recording pre and post control census for about two months (8 weeks), based on the number of bait eaten accumulation, rat mortality, and the percentage of fresh damage to fruit bunches. The results showed that the relative efficacies (control success) rate of bromadiolone (0,005% in the wax cake) place under oil palm canopy was highest, followed by brodifacoum (0.005%, ready mix block) place under oil palm canopy and coumatetralyl (0,0375% in the wax cake), place under oil palm canopy, but the bait place on the leaf midrib were ineffective. Keywords: Field efficacy, brodifacoum, bromadiolone, coumatetralyl, rat pest, oil palm.